2022
DOI: 10.3390/plants11131776
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of Stilbene Synthase Genes in Arachis hypogaea in Response to Methyl Jasmonate and Salicylic Acid Induction

Abstract: Stilbene synthase is an important enzyme of the phenylpropanoid pathway, regulating the production of several biologically active stilbenoids. These compounds have antioxidant, anti-inflammatory, and anti-cancer properties. However, the detailed characterization of stilbene synthase genes in Arachis hypogaea has not yet been performed. In this study, the comprehensive characterization of stilbene synthase genes in A. hypogaea was conducted, commencing with identification, phylogenetic analysis, and study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…Likewise, W-box elements (WRKY-binding sites) are also found in the promoter regions of some primary and specialized metabolism genes, including CHS and PAL [56]. Some of the most frequent elements found in this study (Box 4, ABRE, G-Box, ARE, and CGTCA-and TGACG-motif) were also identified in the promoter regions of four A. hypogaea STS genes, suggesting that they may be responsible for the regulation of STS expression during biotic and abiotic stress responses through MeJA and SA signaling [43].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Likewise, W-box elements (WRKY-binding sites) are also found in the promoter regions of some primary and specialized metabolism genes, including CHS and PAL [56]. Some of the most frequent elements found in this study (Box 4, ABRE, G-Box, ARE, and CGTCA-and TGACG-motif) were also identified in the promoter regions of four A. hypogaea STS genes, suggesting that they may be responsible for the regulation of STS expression during biotic and abiotic stress responses through MeJA and SA signaling [43].…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have identified and characterized members of CHS and STS gene families in peanut (A. hypogaea), whereas there have been no reports on these families on wild Arachis species [43][44][45][46]. The allopolyploid domesticated peanut, with an AABB genome, arose from natural hybridization between the diploid ancestors A. duranensis (genome A) and A. ipaënsis (genome B), followed by spontaneous chromosome duplication [23].…”
Section: Discussionmentioning
confidence: 99%
“…The promoters of genes from several groups harbored a CGTA motif (Figure S24). The CGTA motif is a potential jasmonic acid (JA)‐responsive element (Qayyum et al., 2022). JA was reported to regulate flower development (Yuan & Zhang, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…PAL and STS1 genes are linked to phenylpropanoids [49,50], specialized metabolites related to plant defense against biotic and abiotic stresses. Phenylpropanoids can act indirectly by either through signaling molecules or through toxic effects caused by phytoanticipins, that are common compounds present in plant tissues, and phytoalexins, which are bioactive substances that are produced by a plant in response to the detection of pathogens, such as fungi, bacteria, and virus [51].…”
Section: Discussionmentioning
confidence: 99%